PENTINGNYA PERAN ORANG TUA DALAM MENDUKUNG MANAJEMEN SEKOLAH - Suriyah; Erniza Tri Kurniati; Siti Patimah; M.Makhrus Ali (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
The role of parents in school management is a crucial aspect that is often overlooked in educational discussions. Research shows that parental involvement not only has a positive impact on student academic achievement but also influences the overall school climate. Good collaboration between parents and schools can create an environment that is conducive to student development while increasing the effectiveness of school management. In this study, we will discuss the importance of the role of parents in supporting school management. Using data and case examples from various sources, this study aims to illustrate how collaboration between parents and schools can make a significant contribution to the success of educational institutions. The results of this study are expected to provide a deeper understanding of the importance of synergy between families and schools in realizing a quality education system.